2016
DOI: 10.1111/ijag.12256
|View full text |Cite
|
Sign up to set email alerts
|

A new twist on glass: A brittle material enabling flexible integrated photonics

Abstract: Glass is in general brittle and therefore usually cannot sustain large deformation. Recent advances in glass material development as well as micro‐mechanical designs, however, are set to defy the conventional wisdom through the demonstration of flexible integrated photonics that can be bent, twisted, and even stretched without compromising its structural integrity and optical performance. In this paper, we review the latest progress in this emerging field, and discuss the rational material and mechanical engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…The SU-8 membrane can be delaminated from the handler substrate after detector fabrication to form free-standing flexible devices. This process, which has previously been adopted for flexible ChG photonic device fabrication by the authors [61][62][63][64][65] , capitalizes on the low deposition and processing temperatures of ChG's to facilitate direct integration on polymers which typically cannot withstand temperatures above 250 °C. The Ge23Sb7S70 glass waveguide dimensions are as follows: ridge width 0.8 m, slab thickness 0.13 m and ridge height 0.3 m.…”
Section: Section XII -Fabrication and Characterization Of Flexible Wamentioning
confidence: 99%
“…The SU-8 membrane can be delaminated from the handler substrate after detector fabrication to form free-standing flexible devices. This process, which has previously been adopted for flexible ChG photonic device fabrication by the authors [61][62][63][64][65] , capitalizes on the low deposition and processing temperatures of ChG's to facilitate direct integration on polymers which typically cannot withstand temperatures above 250 °C. The Ge23Sb7S70 glass waveguide dimensions are as follows: ridge width 0.8 m, slab thickness 0.13 m and ridge height 0.3 m.…”
Section: Section XII -Fabrication and Characterization Of Flexible Wamentioning
confidence: 99%
“…The design concept has gradually been applied to fabricate flexible and stretchable photonic sensors. Li et al developed a stretchable serpentine‐shaped waveguide based on brittle glass, as shown in Figure a . The flexible integrated waveguide could be bent, twisted, and stretched.…”
Section: Structural Design For Stretchabilitymentioning
confidence: 99%
“…The PDMS layer functions as the substrate, whereas SU-8, having an intermediate CTE of 52 ppm, is sandwiched between Ge23Sb7S70 glass and PDMS to relieve thermal stress caused by the CTE mismatch between PDMS and glass. at 0% strain and (c) the same device at 36% tensile strain; (d) measured optical loss in a microresonator prior to and after a mechanical fatigue test consisting of 3,000 stretching cycles at 42% tensile strain (33). Fig.…”
Section: Stretchable Integrated Photonicsmentioning
confidence: 99%